Optimal methods for identification of dominants for submerged aquatic vegetation on a case of the northwestern Tatar Strait - A. A. Dulenin (Известия ТИНРО)
Dominant species are identified at infracenotic level for aquatic vegetation in the sublittoral zone of the northwestern Tatar Strait (Japan Sea) on the data collected in 2010–2019. Seven different methods of the identifying are considered based both on visual qualitative and quantitative assessments and on instrumental estimations of abundance for 44 macrophyte species. Depending on applied method, 19–25 species (7–22 % of total number of species) are identified as the dominants, including 10 species identified by all methods. List of these 10 species is defined as the core of vegetation that determines its general properties and the species are determined as unconditional dominants, in opposite to other ones identified by at least one method — conditional dominants. All macrophyte species in areas of low abundance do not meet the dominance criteria. All lists of dominants, including those based on visual estimates of projective cover and its physiognomy, are statistically indistinguishable (p = 0.55–0.92, by pairs of lists) and highly similar (Bray-Curtis index 0.80–0.95, Jacquard index 0.65–0.87), with one exception for the list identified by the method of ranking for the average projective cover (indices of similarity with other lists: 0.68–0.71 by Bray-Curtis, 0.46–0.56 by Jacquard). This visual method of projective cover assessment is combined with the procedure of species dividing to dominant and non-dominant groups. Quantitative criteria of projective cover and biomass, by species (thresholds 0.2 and 1.0 kg/m3, respectively) are used for dividing on cenotic and landscape levels and ranking with Brotskaya-Zenkevich index and its modification for projective cover is used for dividing on regional level. Visual methods are available for verification, but the lists of dominants based on visual and instrumental assessments should be mutually verified.